VD_FINDINFO HC / 2019 / 543 vom 27. Juni 2019 - VD Tribunal cantonal (2019)
DROIT DE PASSAGE, ACTION EN CESSATION DE TROUBLE, INTERPRÉTATIONSENS GÉNÉRAL | 737 CC, 738 CC, 973 CC, 308 al. 1 let. a CPC (CH)